Molecular Detection of Linezolid Resistance Determinants and Identification of a Novel C2626T Mutation in Clinical Isolates of Enterococcus Species from India - Madhumala Shanmugasundaram; MuthuLakshmi BackiaSubramanian; Shanthi Mariappan; Uma Sekar; Kennedy Kumar Palraj; Binesh Lal Yesudhason; Rhea Michelle J. Khodabux (Antibiotics, 2026)
Background: Enterococcus species have emerged as significant multidrug-resistant nosocomial pathogens. Linezolid remains a vital last-resort therapeutic option for the management of severe infections caused by vancomycin-resistant Enterococci. However, resistance to linezolid occurs through several mechanisms, including the presence of the cfr, cfr(D), and optrA genes, as well as mutations in domain V region of the 23S ribosomal RNA gene. This study aimed to detect and characterize linezolid resistance in clinical Enterococcus species. Methodology: A total of 266 clinical isolates belonging to the Enterococcus species were analyzed in this study. Antimicrobial susceptibility testing was performed using the disc diffusion method. The Minimum Inhibitory Concentration (MIC) of linezolid was determined by the agar dilution technique. PCR was performed to detect the presence of cfr, cfr(D), and optrA genes, along with mutations in domain V of the 23S rRNA gene. Results: Among the 266 isolates analyzed, 25 (9.4%) were found to be resistant to linezolid, with MIC values ≥ 8 µg/mL. Of these resistant isolates, the cfr gene was detected in one isolate, cfr(D) in sixteen isolates, and optrA in nine isolates. Notably, four isolates carried mutations in the domain V region of the 23S rRNA gene, including a novel C2626T mutation (in India) along with the previously reported G2592T mutation. Conclusions: This study reports the detection of cfr- and cfr(D)-mediated linezolid resistance among Enterococcus species in India. Furthermore, the presence of optrA and a novel C2626T mutation, alongside the G2592T mutation, was identified among resistant isolates. These findings underscore the urgent need for molecular surveillance to prevent further dissemination of these multidrug-resistant pathogens.